TRIP GENERATION MODEL OF APARTMENT DWELLERS AT BANDUNG ( CASE STUDY : AHMAD YANI GATEWAY APARTMENT) - RICHARDO (NIM : 25414048), HARRY
Increasing population will affect the growth of housing, city facilities, and transportation. Limited land and high land prices and the increasing popularity of the property business in Indonesia, especially in big cities gave rise to variations in the type of occupancy of the multi-floor system known as Apartment. One of the apartments that has been operating in the city are the Gateway Ahmad Yani apartment is located on Jalan Ahmad Yani No. 669. With the Gateway Apartment Ahmad Yani will inevitably lead to rise of traffic that will weigh on certain road network especially Jalan Ahmad Yani are directly connected with the exit-entrance area of the apartment This study aimed to obtain a model of trip generation residents of the apartment Gateway Ahmad Yani Bandung. The analytical method used is regression method using independent variables: the total number of family members (X1), the total number of family members over the age of 5 years (X2), the number of family members who have a SIM (X3), the number of family members working (X4), number of family members attending school (X5), number of cars owned (X6), the number of motorcycles owned (X7), age of the head of the family (X8), total household income (X9) and the dependent variable is the number trip apartment dwellers were reviewed based on peak hours in the morning (6:00 to 8:00), during the peak hours (12:00 to 14:00) and afternoon peak hours (16:00 to 6:00 p.m.). Based on the results obtained by the analysis with SPSS trip generation model of apartment dwellers in the form of a mathematical equation. Model for Monday in the morning peak hour was Y = - 0.168 + 0.284 X2 + 0.232 X7, this model once transformed into a form of trip rate generates the greatest value of the trip rate is 0.432 smp / unit. Six of the nine independent variables affect the trip generation models generated apartment dwellers. This suggests that the socio-economic parameters household significant impact on trip generation residents of the apartment.